Artificial UV and natural ageing of polycarbonate/poly(butylene terephthalate) binary blend and reprocessing of aged blends - Kuram, Emel; Ozcelik, Babur; Sarman, Omer Faruk; Kocoglu, Hurol; Ayas, Hamza; Dogan, Mehmet (Sage Publications Ltd, 2025)
In this research, the effect of reprocessing for aged polycarbonate (PC)/poly (butylene terephthalate) (PBT) blends was determined on the mechanical properties (tensile, impact, flexural), melt flow index and morphology. Virgin PC/PBT blends were injection molded as the tensile, flexural and impact samples to evaluate the mechanical, rheological, and morphological properties. After that, samples were exposed to artificial accelerated ageing in an QUV chamber (simulating outdoor weathering with alternating cycles of ultraviolet (UV) light and moisture at controlled elevated temperature) for up to 336 hours and natural ageing in Gebze (Turkey) for up to 1 year between May 2017 and May 2018. After these ageing processes, naturally and UV aged specimens were ground, and the ground specimens were mixed with virgin PC/PBT blends at different ratios (25%, 50% and 75% by weight). The mixed materials were re-molded to fabricate test specimens and then characterized. In summary, in current study, the mechanical, rheological, and morphological properties of virgin, aged in natural for 12 months, aged in UV chamber for 336 hours and mixture of virgin-aged PC/PBT were investigated.
Keywords: Natural ageing; UV ageing; reprocessing; tensile properties; impact strength; flexural properties; PC/PBT